Examining the Impact of Public Engagement and Presidential Leadership Communication on Social Media in China: Implications for Government-Public Relationship Cultivation. Issue 3 (27th May 2018) - Men, Linjuan Rita; Yang, Aimei; Song, Baobao; Kiousis, Spiro
ABSTRACT: This study examined how public positive and negative social media (i.e., WeChat) discussion about President Xi Jinping in China, along with Xi's leadership communication styles of assertiveness, responsiveness, and authenticity on social media influence publics' evaluation of his leadership effectiveness, which in turn, influences public trust and satisfaction with the government. Through a quantitative online survey of 396 WeChat users in China, randomly selected via an international sampling firm and a structural equation modeling analysis, the results show that publics' political discussion about Xi on social media in China significantly influences the perceived leadership effectiveness of the president. Specifically, the more the publics engage in positive discussion about the president on social media, the more they perceive him to be a better political leader, and vice-versa. The president's leadership communication attributes of responsiveness and authenticity strongly and positively influenced perceived leadership effectiveness and the quality of government-public relationships. Publics' evaluation of the president's leadership effectiveness directly contributed to public trust and satisfaction toward the government. The theoretical and practical implications of the study are discussed.